Lexicographie artistique; Artistic lexicography formes, usages et enjeux dans l'Europe moderne; forms, uses and issues in Early Modern Europe - Heck, Michèle-Caroline (Théorie des Art, 2018)
In crossed approaches, the themes developed in this book bring a new look at the forms, uses and stakes of artistic lexicography in modern times. In a perspective of circulation of concepts and practices, and permeability of the artistic borders, the word proves to be a precious laboratory of the practice of the artistic practice and a field of exploration of the cultural networks that cross and make Europe . Through the development of a language, books on art whose publications are growing in the north of the Alps from 1600, aim at the construction of a common knowledge for the use of painters and amateurs. Their many translations, published since the modern era, also testify to their role of diffusion agent in constant adaptation to the readership to which they are addressed. Understanding strategies and processes of invention and transfer of specific terminology to aesthetic expression becomes an important issue. Words, indeed, are not interchangeable. By succeeding or overlapping, even if they are contradictory, the different senses give thickness and subtlety to the concept. The journey of a notion into time and space also contributes to broadening our understanding of a cultural history between universality and identity within the artistic diversity that characterizes modern Europe.